Formation Silver Nanoparticles of Different Size Using Different Reductants with AgNO3 Solution - Haider , Awiyada J.; Abed, Ali L.; Ahmed , Duha S. (Iraqi Journal of Science, 2022)
In this study, silver nanoparticles (AgNPs) are synthesized using different chemical routes to obtain different sizes and shapes of nanoparticles by colloid chemistry with using stabilizing and reducing agent, which make them interesting for variety of physical applications. The morphology and structure of the synthesized AgNPs were characterized by UV-VIS spectra, Scanning Electron Microscopy (SEM) and Zeta potential to demonstrate that different sizes and shapes can by synthesized by different reductants in the presence of various stabilizing agents.